The Effect of Neck Massage Using Olive Oil on Headache Pain Intensity in Hypertensive Patients: A Case Study - Wayunah Wayunah; Syafunnuril Anwar H; Fadhila Maulidina; Vina Yulianti; Dwi Widyawati; Agi Ginanjar (Yayasan Inspirasi El Burhani, 2026)
Introduction: Hypertension is a major global health problem and often accompanied by subjective complaints such as headache and neck stiffness, which may reduce patients’ quality of life. Non-pharmacological nursing interventions are needed to complement pharmacological therapy in managing pain among hypertensive patients. One alternative intervention is neck massage using olive oil, which promotes muscle relaxation and improves local blood circulation. Objective: This study aimed to describe the effectiveness of neck massage using olive oil in reducing headache intensity in patients with hypertension. Method: This research employed a descriptive case study design involving two hypertensive patients who experienced headache in the working area of Kahuripan Primary Health Center, Tasikmalaya. The intervention consisted of neck massage using olive oil for 10 minutes once daily over three consecutive days. Pain intensity was measured before and after each session using the Numeric Rating Scale (NRS). Data were analyzed descriptively by comparing pain scores before and after the intervention. Result: Both respondents experienced a consistent decrease in headache intensity following the intervention. The first respondent showed a total reduction of four points (from 6 to 2), while the second respondent showed a reduction of three points (from 5 to 2) over three days of treatment. Conclusion: Neck massage using olive oil was effective in reducing headache intensity among hypertensive patients. This intervention can be recommended as a complementary non-pharmacological nursing therapy to improve patient comfort alongside standard pharmacological management.